Thermal properties of minor actinide targets. (July 2015) - Staicu, D.; Somers, J.; Fernandez, A.; Konings, R.J.M.
Abstract: The thermal properties of minor actinide targets for the management of high level and long lived radioactive waste are investigated. The microstructure, thermal diffusivity and specific heat of (Pu, Am)O2, (Zr, Pu, Am)O2, (Zr, Y, Am)O2, (Zr, Y, Pu, Am)O2 and CERMETS with Mo matrix are characterised in order to assess the safety limits of these materials. Highlights: Specific heat, thermal diffusivity and conductivity obtained for Am containing solid solutions and CERCERS with Mo matrix. The conductivity of (Zr, Pu, Am)O2, (Zr, Y, Am)O2 and (Zr, Y, Pu, Am)O2 is low and almost temperature independent. CERMETs with 13 to 39 vol. % inclusions have a conductivity higher by a factor 20 to 40 compared to the solid solutions.